Emotional expression in psychiatric conditions: New technology for clinicians. Issue 2 (25th December 2018) - Grabowski, Karol; Rynkiewicz, Agnieszka; Lassalle, Amandine; Baron‐Cohen, Simon; Schuller, Björn; Cummins, Nicholas; Baird, Alice; Podgórska‐Bednarz, Justyna; Pieniążek, Agata; Łucka, Izabela
Abstract : Aim: Emotional expressions are one of the most widely studied topics in neuroscience, from both clinical and non‐clinical perspectives. Atypical emotional expressions are seen in various psychiatric conditions, including schizophrenia, depression, and autism spectrum conditions. Understanding the basics of emotional expressions and recognition can be crucial for diagnostic and therapeutic procedures. Emotions can be expressed in the face, gesture, posture, voice, and behavior and affect physiological parameters, such as the heart rate or body temperature. With modern technology, clinicians can use a variety of tools ranging from sophisticated laboratory equipment to smartphones and web cameras. The aim of this paper is to review the currently used tools using modern technology and discuss their usefulness as well as possible future directions in emotional expression research and treatment strategies. Methods: The authors conducted a literature review in the PubMed, EBSCO, and SCOPUS databases, using the following key words: 'emotions, ' 'emotional expression, ' 'affective computing, ' and 'autism.' The most relevant and up‐to‐date publications were identified and discussed. Search results were supplemented by the authors' own research in the field of emotional expression. Results: We present a critical review of the currently available technical diagnostic and therapeutic methods. The most important studies are summarized in a table. Conclusion: Most of the currently available methods have not been adequately validated in clinical settings. They may be a great help in everyday practice; however, they need further testing. Future directions in this field include more virtual‐reality‐based and interactive interventions, as well as development and improvement of humanoid robots.